Density functional theory study on magnetic interactions in the V3+ dimer complexes1. Issue 6 (21st March 2012) - Suzuki, Hidenori; Satoko, Chikatoshi; Gidopoulos, Nikitas I.; Theophilou, Andreas K.
Abstract The magnetic interactions in the V2Cl 93−<inline-graphic xlink:href="ark:/27927/pgg1tvb0fmx" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> cluster is investigated as an example of the orbitally degenerate d2–d2 transition metal dimer complexes. The local orbital functions are defined by linear combinations of the molecular orbital functions which are calculated by the density functional theory. These local orbitals are used as basis of the matrix of an effective Hamiltonian. To evaluate the parameters of the effective Hamiltonian, the total energies in the single Slater determinants of the all possible configurations are calculated. Especially to obtain the one‐body energies and Coulomb integrals separately, the total energies in the states of the configurations with a noninteger occupation numbers are also calculated. One parameter remains as a fitting parameter Δ, which is the difference between the one‐body energies of two local orbitals a1 and e under C3v site symmetry. The temperature dependence of the magnetic susceptibility for some values of Δ are shown.